Բնության ու բարոյականության հակադրությունը Նար-Դոսի ստեղծագործության մեջ - Մարգարյան, Սիրանուշ
Нар-Дос - один из выдающихся представителей армянской классической литературы. Начав свою литературно-творческую деятельность в трудное историческое время, когда возникло глубокое несоответствие между либеральными мыслителями и национальными консерваторами, писатель связал свою деятельность с «Нор Дар (Новый век)», в соответствии с которым формируя свою эстетическую концепцию. В статье рассматривается проблема противоречия между природой и моралью в искусстве Нар-Доса. Естественно, с приоритетом системы моральных ценностейрешается идея его романов. В этом контексте мы рассматриваемнекоторые из его работ: «Правдивый друг», «Нежные струны», «Зазанян». Nar-Dos is one of the outstanding representatives of Armenian classical literature. Starting his literary-creative activity in difficult historical time when there has been arisen a deep discrepancy between the liberal thinkers and the national-conservatives, the writer connected his activity to “Nor dar (New age)” and according to his aesthetic concept has been formed. The article reviews the problem of contradiction between the nature and the morality in Nar-Dos’s art. Naturally, the idea of his novels is solved with the priority of moral value system. In this context, we are referring to his several works: “True friend”, “Tender strings”, “Zazanyan”.
Keywords: Գրականագիտություն